Exploring the Origin of Dark Matter in the Early Universe - Al Dallal, Shawki; Azzam, Walid; Sakaji, Ammar (European Journal of Applied Sciences, 2026)
Dark matter becomes a crucial component in shaping the structure of our cosmos. Evidence of nonluminous matter became known during the 1930s, as investigations into the Doppler shift in star spectra within the galactic disk revealed inadequacies in explaining the gravitational influence suggested by observed velocities. The confirmation of this discovery was subsequently achieved by assessing the velocity dispersion within abundant galaxy clusters. Galaxy formation models assume the presence of dark matter, considering it an essential foundational element influencing their structural evolution. However, the Big Bang theory struggles to unravel the elusive origin of dark matter, lacking a conclusive model that provides clear insights. In this study, we postulate an eleven-dimensional spacetime, as proposed by string theories, and explore the notion that symmetry breaking catalyzed the formation of two distinct spacetime manifolds. One is the familiar four-dimensional spacetime we observe and experience, while the other represents an additional dimensional manifold dominated by dark matter. To reinforce this point, we examine three existing studies, encompassing both observational and theoretical aspects that strongly support the suggested involvement of dark matter in the universe. Additionally, the proposed model places restrictions on the feasibility of using traditional detection methods to identify dark matter particles, thereby accounting for the absence of their detection thus far.